Fabrication of adjacent micropillar arrays with different heights for cell studies - Wei, Jin; Shi, Jian; Wang, Bin; Tang, Yadong; Tu, Xiaolong; Roy, Emmanuel; Ladoux, Benoit; Chen, Yong (Microelectronic Engineering, 2016)
We fabricated adjacent micropillar arrays with different heights using different materials. Masters are obtained by using a two-step photolithography technique. A thin layer of SU8-3005 resist was spin coated on a chromium mask, followed by a front side exposure with another assistance mask, resulting in a step resist profile. Then, a thin layer of SU8-3010 resist was spin-coated again on the mask, followed by a back side exposure. The master patterns which consist of adjacent pillar arrays of different heights were replicated into polydimethylsiloxane (PDMS) by soft lithography. The PDMS replicas were then used as molds for casting or hot embossing, resulted in final pillars arrays in PDMS, poly lactic-co-glycolic acid (PLGA) and flexestene thermoplastic elastomer. Such substrates made of different materials were used to evaluate the surface stiffness dependent cell migration of NIH 3T3 cells. Our results show that the cells were sensitive to the height of PDMS pillars, due to their comparable Young's module, and that the cells were preferentially localized on the stiffer surfaces. However, no such effect was observed when the cells were placed on the PLGA substrate because of the excessive rigidity of the PLGA pillars.
CRIS-Team Scopus Importer:2024-02-19
Keywords: Cell culture; Cell-materials interaction; Micro pillars array